Territorial work, participation and production. Explanatory keys to understand the achievements of a local development project in the western Pampas (2015-2023) (Huellas, 2024)
This article presents the reconstruction and analysis of the territorial work of Cooperativa La Comunitaria in the rural town of Santa Isabel (province of La Pampa), and more precisely, the opening of a balanced feed plant and the creation of an alternative corn marketing circuit. From the perspective of local development, the aim is to analyze the results of La Comunitaria's intervention in the territory at a productive level and the degree of replicability this project can have in other rural territories. To do this, we will recover the historical-political background of La Comunitaria at the local level, we will investigate the articulations that the organization establishes with other actors and its power construction strategies. On the other hand, we will study the organizational and economic features and the experiences of participation in the productive project. This is a qualitative work, which includes field records (both in-person and virtual) and a transdisciplinary theoretical approach. It is expected to make a contribution to the field of studies of public policies linked to local development, the social economy, as well as rural studies in general.
Keywords: territory, local development, participation, social economy